Preoperative and operative risk factors for failed lateral collateral ligament reconstruction - Shawn W. O’Driscoll, MD, PhD; Grace K. Chaney, BS (JSES International, 2023)
Repair or reconstruction of the lateral collateral ligament (LCL) using autograft or allograft is a well-accepted treatment of posterolateral rotatory instability. The prevalence and causes for failure of LCL reconstruction are not well documented in the literature. Any approach to the assessment and management of failed LCL reconstruction must begin with understanding the risk factors for failure in the first place. Such understanding would likely make many failures preventable as well. In our experience, there are a number of identifiable preoperative risk factors concerning bony and/or soft tissue constraints for failure of LCL reconstruction. There are also operative factors such as tunnel and graft placement as well as excessive lateral condyle stripping that play a role in risk of failure. This report is an attempt to provide a systematic approach to identifying and managing the preoperative and operative risk factors. Further studies are warranted to determine the indications for, and success rates of surgical intervention in managing these risk factors.